Pid controller design for second-order delayed unstable process - Truong, Nguyen Luan Vu; Le, Hieu Giang; Le, Linh; Vo, Lam Chuong; Phan, Tan Hai (Journal of Technical Education Science, 2017)
In this paper, a proportional-integral-derivative (PID) controller cascaded with a second-order lead-lag filter is proposed for unstable second-order process with time delay. On the basis of the internal model control (IMC) principle for the two-degree-of-freedom (2DF) control system, the proposed method can achieve the enhanced performance for both disturbance rejection and set-point tracking problems. Several illustrative examples are included to demonstrate the improved performances of proposed controllers in compared with those of recently published PID-type controllers, since the various controllers are all tuned to have the same degree of robustness by measuring the maximum sensitivity (Ms) value